Quality Characteristics of Fermented Arabica CascaraTea using SCOBY-Kombucha Fermentation in Different Drying Methods - Nur Faidah Munir; Muhammad Kadir; Suwandi Suwandi; Reta Reta (International Journal Science and Technology, 2026)
Arabica coffee processing generates coffee cherry skin or husk as a by-product that is often underutilized and treated as waste, despite its potential to be processed into cascara tea as a value-added functional beverage. The application of SCOBY-kombucha fermentation offers an innovative approach to improve the chemical and sensory quality of cascara tea. Objective: This study aimed to analyze the quality characteristics of cascara tea produced from Arabica coffee husks fermented with SCOBY-kombucha under different drying methods. Method: This study employed a quantitative experimental approach using a completely randomized design (CRD). The treatments consisted of fermentation and non-fermentation combined with two drying methods, namely tray-dryer and sun-dryer. Data were collected through laboratory analysis of moisture content, total phenol content, and tannin characteristics, as well as organoleptic testing of color, aroma, and taste. The data were analyzed using analysis of variance (ANOVA). Results: The results showed that drying methods had no significant effect on the quality of cascara tea in terms of moisture content and total phenol content. However, SCOBY-kombucha fermentation reduced tannin content and improved the aroma characteristics of the tea. The best treatment was obtained from SCOBY-kombucha fermentation combined with tray-dryer drying, producing cascara tea with 4.8% moisture content, total phenol content of 1191.6 mg GAE/100 g, lower tannin content, and acceptable sensory characteristics. Implications: The findings indicate that fermentation can enhance the quality and consumer acceptability of cascara tea, while supporting the utilization of coffee-processing by-products into value-added products in the agroindustrial sector. Originality/Value: This study provides a novel contribution by integrating SCOBY-kombucha fermentation and drying methods in cascara tea production, offering a comprehensive evaluation of their combined effects on chemical and sensory quality.